High casein concentration induces diarrhea through mTOR signal pathway inhibition in post-weaning piglets - Gao, Jing; Ma, Li; Yin, Yulong; Chen, Yongzhong; Li, Tiejun (Frontiers in Microbiology, 2024)
Weaning is one of the most challenging periods in a pig’s life, during which piglets suffer from nutrition and other issues. Post-weaning diarrhea is one of the major health problems in the pig industry, leading to high morbidity and mortality rates. Previous studies have demonstrated that both the source and concentration of proteins are closely associated with post-weaning diarrhea in piglets. This study was conducted to prevent and control post-weaning diarrhea by selecting different dietary protein concentrations. To eliminate interference from other protein sources, casein was used as the only protein source in this study. Fourteen piglets (weighing 8.43 ± 0.3 kg, weaned on the 28th day) were randomly assigned to two dietary protein groups: a low-protein group (LP, containing 17% casein) and a high-protein group (HP, containing 30% casein). The experiment lasted 2 weeks, during which all piglets had ad libitum access to food and water. Diarrhea was scored on a scale from 1 to 3 (where 1 indicates normal stools and 3 indicates watery diarrhea), and growth performance measurements were recorded daily. The results showed that the piglets in the HP group had persistent diarrhea during the whole study, whereas no diarrhea was observed among piglets in the control group. The body weights and feed intake were significantly lower in piglets in the HP group compared to those in the LP group (p < 0.05). The gastrointestinal pH was significantly higher in piglets in the HP group than those in the LP group (p < 0.05). The intestinal tract microorganisms of the piglets in both groups were significantly affected by the protein concentration of the diet. A diet with high casein concentration significantly reduced the microbiota diversity. Compared to the LP group, the 30% casein diet decreased the abundance of Firmicutes, Bacteroidetes, and Actinobacteria at the phylum level and the relative abundance of Ruminococcus at the genus level. Diarrhea-related mRNA abundances were analyzed by the real-time polymerase chain reaction (PCR) in the intestine of piglets, and the results showed that the HP concentration markedly decreased the expression of solute carriers (SLC, p < 0.05). The mammalian target of rapamycin-mTOR signaling pathway (p < 0.01) was activated in the HP group. In conclusion, a high-protein diet induced post-weaning diarrhea, decreased growth performance, increased gastrointestinal pH, and reduced expression of solute carrier proteins. However, the relationship between high dietary casein feed and post-weaning diarrhea remains unclear and needs to be explored further.